The Challenges of Science Education in Secondary School Level: A Case Study from Chakaria Upazila of Cox‟s Bazar District (Bangladesh Journal of Public Administration, 2019)
In the present context of the fourth Industrial Revolution, science education is considered as theappropriate tool for the development of a nation. Accordingly, the government of Bangladesh has laidsignificant emphasis on science and technology education as a gateway to development with anaspiration to build a „Digital Bangladesh‟ and to attain the status of a middle-income country by2021. However, contrasting to a large number of government initiatives, a declining scenario ofenrollment in science groups at the secondary level has been reported for nearly a decade. Thissituation is likely to be worse in rural areas as it was evident from a visit to Chakaria Upazila ofCox‟s Bazar. Drawing attention to the underlying problems of science education, this study attemptsto provide an account of the present scenario of science enrollment at secondary school level in therural Bangladesh, and identifies the factors responsible for the enrollment pattern. The ten years‟trend analysis on science group enrollment provided a clear picture of declining scenario since 2010.Compared to the other two groups of Business and Humanities, preferences to be enrolled in theScience group at secondary level steadily showed a marked decrease from 2009 to 2018. Complexityand volume of the science syllabus creating “Science Fear”, weak teaching capacity, shortage ofscience and mathematics teachers, scarcity of teaching materials and paucity of laboratory equipmentwere found to be the key factors responsible for declining science enrollments in the secondary levelof rural Bangladesh.